Culture of a Planktonic Cyclopoid, Apocyclops Dengizicus (Lepeshkin, 1900) and Its Suitability as Live Feed for the Postlarvae of Giant Black Tiger Shrimp, Penaeus Monodon Fabricus (1798) - Farhadian, Omidvar (2006)
Copepods form an important link between phytoplankton and higher trophic levels such as fish and shrimp. In aquaculture industry, some species of copepods are used as live feed for fish and shrimp larvae. In this study the suitability of a copepod Apocyclops dengizicus as a live food was investigated. For establishment of successful culture protocol, the biology (feeding, reproduction, and growth) and environmental requirements (salinity, temperature, light intensity, and photoperiod) of A. dengizicus were studied